Pregnancy and the Long-Acting Insulin Analogue: a Case Study - Caronna, S.; Cioni, F.; Dall'Aglio, et al., E. (Acta Biomedica Atenei Parmensis, 2006)
R.S. is a 22 years old Caucasian woman suffering from obesity, hypertension and Type I Diabetes Mellitus since the age of 6 years. Type I DM treatment includes 3 insulin injections at meal time and one glargine injection at bedtime. The insulin therapy regimen was prolonged during pregnancy and continued after childbirth. Optimal glycemic compensations were monitored throughout the pregnancy using HbA1c variations and other standard controls included in the OBG routine protocols, all within normal values. The pregnancy ended at the 38th week of gestation with a caesarean birth, during which a 3,54 Kg healthy boy with an APGAR of 9 was born. Both the mother and the newborn resulted in perfect health conditions confirming that the possibility of using glargine insulin profiles during pregnancy in selected cases with close monitoring may exist.